Effect of Very Low Intensity Weight Squat Exercises ( - Arga Arga; Muhammad Arkanul Arba'; Siti Nurhalizah Mutia Aulria; Charmila Tandi Rerung (Universitas Pejuang Republik Indonesia, 2025)
Background: Leg strength is a fundamental physical component required by sports coaching education students to support both their academic practical activities and future professional roles as sports coaches. Traditional resistance training guidelines generally recommend moderate-to-high intensity loads (>60% 1-RM) to elicit meaningful strength gains. However, very low-intensity squat training combined with techniques such as slow-tempo execution and reduced rest intervals has recently emerged as a potential alternative for inducing strength adaptations, particularly for individuals seeking joint-friendly training options. Empirical evidence regarding the effectiveness of very low-intensity squat training in producing leg strength gains among sports coaching education students remains limited. Objectives: This study aimed to analyze the effect of very low-intensity squat training (<30% 1-RM) on leg strength among sports coaching education students. Methods: This study employed a quantitative approach using a Pre-Experimental One Group Pretest-Posttest Design. The participants consisted of 38 sports coaching education students selected through purposive sampling. The intervention was conducted over eight weeks with a frequency of three sessions per week, in which participants performed back squat exercises at an intensity below 30% of their one-repetition maximum (1-RM), executed with slow tempo and short inter-set rest intervals to maximize time under tension and metabolic stress. Leg strength was assessed using the back squat 1-RM test, while leg power was assessed using the standing broad jump test. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, and Paired Sample t-Test at a significance level of α = 0.05. Results: The findings revealed significant improvements in leg strength and power following the intervention. Back squat 1-RM increased from 52.36 ± 9.14 kg to 64.78 ± 10.27 kg, representing a 23.73% improvement (p = 0.000). Standing broad jump distance increased from 178.42 ± 14.36 cm to 196.85 ± 13.92 cm, representing a 10.33% improvement (p = 0.000). Conclusions: Very low-intensity squat training (<30% 1-RM) performed with slow tempo and short rest intervals significantly improves leg strength and power among sports coaching education students, suggesting that this training approach is a viable, joint-friendly alternative to conventional high-intensity resistance training for enhancing lower-limb strength in this population.